Entrepreneurial Orientation, MSME Growth and the Mediating Role of Firm Strategic Capabilities in the Manufacturing Sector in Nairobi County, Kenya - Mosonik, John K.; Maru, Loice C.; K. Komen, Joyce (International Journal of Scientific Research and Management (IJSRM), 2021)
Growth among Micro, Small and Medium-sized Enterprises (MSME) is of eminence to economic progression in both developed and developing economies, credited for employment creation, driving innovation and contribution to Gross Domestic Product (GDP) in both contexts. Whereas entrepreneurial orientation has been identified to underpin MSME growth, several studies on entrepreneurial orientation -growth nexus have provided mixed results based on the aggregated one-dimensional measure of entrepreneurial orientation. While some report a significant association, some report no significance. The mixed findings imply that the relationship between entrepreneurial orientation and growth is not linear, pointing to other causal factors either internal or external to the enterprise. against this backdrop, this study set out to assess the mediating effect of firm strategic capabilities on the relationship between entrepreneurial orientation and growth of manufacturing sector MSMEs in Kenya. Anchored on the contingency fit view, the resource-based view and the life-cycle theory, the study adopted a positivist approach, employing the explanatory research design of a cross sectional nature. With a target population of 98,607, a stratified sample of 384 MSMEs from the manufacturing sector in Nairobi County was drawn. Data was collected by use of structured questionnaires and analyzed by both descriptive and inferential statistics including Pearson correlation and regression analyses. The study controlled for both age and sub-sector, as they have been previously found to affect firm growth. Results indicate that entrepreneurial orientation has a significant effect on firm strategic capabilities (β = .276, p = .000